A comparison of neuroprotective efficacy of the oxime K203 and its fluorinated analogue (KR-22836) with obidoxime in Tabun-poisoned rats - Kassa, Jiri; Karasova, Jana Zdarova; Tesarova, Sandra; Musilek, Kamil; Kuca, Kamil; Jung, Young-Sik (Basic & clinical pharmacology & toxicology, 2010)
The ability of the newly developed bispyridinium compound K203 and its fluorinated analogue KR-22836 to reduce tabun-induced acute neurotoxic signs and symptoms was compared with the currently available reactivator of acetylcholinesterase-obidoxime. Tabun-induced neurotoxicity and the neuroprotective effects of all tested oximes in combination with atropine in rats poisoned with tabun at a sublethal dose (200 μg/kg intramuscularly (i.m.); 80% of LD(50) value) were monitored by a functional observational battery at 24 hr after tabun challenge. The results indicate that all tested oximes combined with atropine were able to survive tabun-poisoned rats 24 hr after tabun challenge while one non-treated tabun-poisoned rat died within 24 hr after tabun poisoning. All tested oximes combined with atropine were able to decrease tabun-induced neurotoxicity in the case of sublethal poisoning but they did not eliminate all tabun-induced acute neurotoxic signs and symptoms. While the ability to reduce tabun-induced acute neurotoxicity of obidoxime and K203 was similar, the neuroprotective efficacy of KR-22836 was slightly higher compared to other tested oximes. Thus, the newly developed fluorinated analogue of K203, called KR-22836, is able to slightly increase the neuroprotective effectiveness of antidotal treatment of acute tabun poisonings compared to K203 and currently available obidoxime.
Keywords: Animals; Chemical Warfare Agents; Acute Disease; autonomní nervový systém; neurotoxické syndromy; Rats, Wistar; Neurotoxicity Syndromes; Autonomic Nervous System; svalový tonus; hyperkineze; výsledek terapie; oximy; otrava organofosfáty; Pyridinium Compounds; Muscle Tonus; Molecular Structure; pyridinové sloučeniny; chování zvířat; chemické bojové látky; Treatment Outcome; Organophosphates; molekulární struktura; Oximes; Male; Neuroprotective Agents; Obidoxime Chloride; organofosfáty; obidoxim chlorid; krysa rodu Rattus; Behavior, Animal; akutní nemoc; Hyperkinesis; zvířata; mužské pohlaví; Organophosphate Poisoning; Rats; potkani Wistar; neuroprotektivní látky